Annual World Bank Conference on Development in Latin America and the Caribbean, 1997 : Trade, towards open regionalism:proceedings of a conference held in Montevideo, Uruguay - Burki, Shahid Javed; Burki, Shahid Javed; Calvo, Sara.; Perry, Guillermo E. (Washington, D.C.: The World Bank, 1998)
This third Annual Bank Conference on Development in Latin America and the Caribbean (LAC) focuses on trade liberalization policy, specifically " open regionalism, " a term coined to describe the fact that 1) regionalism has gone hand in hand with unilateral trade opening:statistics on tariff and non-tariff measures affecting imports show that protectionist policies have been dismantled in the major LAC countries during the last decade; 2) regionalism has gone hand in hand with a substantial liberalization of investment regimes:provisions, including national treatment provisions, in regional trading arrangements show that several LAC countries treat foreign direct investment on exactly the same footing as domestic investment; and 3) most LAC countries are willing to participate in building a hemispheric free-trade zone and have been active, pro-liberalization members of the World Trade Organization (WTO). Speeches emphasized the political returns from trade integration:reciprocal lock-in, alliances created among pro-reform factions, pro-integration movements across countries, civil society integration, more-likely peaceful settlements to disputes, and general advancement of harmony in the Western Hemisphere through atmospherics, through positive incentive structures, and through cross-country coalitions. Because these positive linkages are largely implicit and not unduly burdensome, they make regional integration consistent with convergence toward global trade integration.
Keywords: Free Trade; International Economics & Trade; Trade Law; Trade Policy; Public Sector Development; Law and Development; Economic Theory and Research; Emerging Markets; Macroeconomics and Economic Growth; Private Sector Development